Analysis of the Interconnection between Digital Skills of Human Resources in SMEs and the Success of Digital Business Strategy Implementation - Sutrisno, Sutrisno; Kraugusteeliana, Kraugusteeliana; Syamsuri, Syamsuri (Institut Riset dan Publikasi Indonesia, 2024)
The advancement of information technology has transformed the way SMEs operate, from marketing aspects to inventory management. Digital business opens up new opportunities for SMEs but also demands new skills from human resources to keep up with these developments. The objective of this research is to analyze the interconnection between the digital skills of human resources in SMEs and the success of implementing digital business strategies. This research method focuses on qualitative literature review using Google Scholar as the data source, especially for articles published between 2021 and 2024. The study results indicate that the role of human resources in an increasingly digital business world is crucial. The digital skills possessed by human resources not only affect the effectiveness of implementing digital business strategies but also impact the competitiveness and sustainability of SMEs in the constantly changing market. A deep understanding of the market, creativity in innovation, and adaptability are important factors in ensuring business success in this digital era.